Development of DIGaKiT: identifying students’ alternative conceptions by Rasch analysis model - Samsudin, Achmad; Azizah, Nurul; Fratiwi, Nuzulira Janeusse; Suhandi, Andi; Irwandani, Irwandani; Nurtanto, Muhammad; Yusup, Muhamad; Supriyatman, Supriyatman; Masrifah, Masrifah; Aminudin, Adam Hadiana; Costu, Bayram (Intelektual Pustaka Media Utama, 2024)
Alternative conceptions become obstacles in physics. However, it is difficult to find instruments that can identify students' alternative conceptions, especially in gases kinetic theory (DIGaKiT). The purpose of this research was to development of diagnostic instrument of DIGaKiT in identifying students’ alternative conceptions by Rasch analysis model. The research method used the defining, designing, developing, and disseminating (4D). The samples are 31 students (12 male students and 19 female students, their ages were typically 16 years old) at one of the senior high schools at Belitung. Rasch analysis was used to identify the validity, reliability, and distribution of students' alternative conceptions. The result is that the level of validity and reliability of the instrument is in a good category. Meanwhile, alternative conceptions of the kinetic theory of gases can be identified in all questions, and the questions with the highest alternative conceptions are questions with code Q11 (77%) and the lowest are questions with codes Q1, Q5, and Q6 (4%). Therefore, teachers must design learning processes that can reduce students’ alternative conceptions of the kinetic theory of gases material.